Strategic Innovation and Technology Adoption in an Evolving Industry - Darren Filson; Richard T. Gretz (Claremont McKenna College, Department of Economics, 2003)
We introduce a racing model with multiple product generations, product innovation, spin-outs, and licensing. Industry conditions and innovation characteristics affect who wins the race and who markets the resulting product. Small firms market their innovations when they pioneer a new generation or improve quality in a young generation and license their innovations in mature generations. If old generation leaders ever market improvements in young generation goods, they do so early on. Leadership in mature generations persists. Tests on the rigid disk drive industry (1977-97) provide empirical support. The results have implications for antitrust policies and policies governing employee non-compete agreements.
Keywords: L63; L41; K31; O38; O31; 330; industry dynamics; employee mobility; innovation market; covenant not to compete; spin-offs; Innovation; Innovationswettbewerb; Technologiewahl; Lizenzvergabe; Magnetischer Speicher; Theorie; Vereinigte Staaten